Lyophilized amorphous dispersion of telmisartan in a combined carrier–alkalizer system: formulation development and in vivo study - Al-Japairai, Khater A. S.; Alkhalidi, Hala M.; Mahmood, Syed; Almurisi, Samah H.; Doolaanea, Abd Almonem; Al-Sindi, Taha A.; Chatterjee, Bappaditya (American Chemical Society, 2020)
Telmisartan suffers from low oral bioavailability due to its poor water solubility. The research work presents a formulation of solid dispersed (SD) telmisartan formulation as a ternary mixture of a drug, a polymeric carrier (poly(vinylpyrrolidone) (PVP) K30), and an alkalizer (Na2CO3). The preparation method, which was lyophilization of an aqueous solution containing the ingredients, was free from any organic solvent. The developed SD formulations resulted in a significant improvement in in vitro dissolution (>90% drug dissolution in 15 min) compared to pure telmisartan. Solid-state characterization by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and X-ray diffraction (XRD) studies indicated the conversion of crystalline telmisartan into an amorphous form. Fourier transform infrared (FTIR) spectroscopy revealed the drug–polymer interaction that was responsible for reducing the chances of recrystallization. A short-term stability study showed that selected SD formulations were stable in terms of in vitro dissolution and retained their amorphous structure in ambient and accelerated conditions over 2 months. Selected formulations (drug/PVP K30/Na2CO3 as 1:1:2 or 1:2:2 weight ratio) resulted in >2.48 times relative oral bioavailability compared to marketed formulations. It was considered that the incorporation of an alkalizer and a hydrophilic polymer, and amorphization of telmisartan by lyophilization, could enhance in vitro dissolution and improve oral bioavailability.